The OPTIMIZATION OF COOPERATION AGREEMENTS BETWEEN IMMIGRATION AND IOM AND UNHCR IN THE HANDLING OF ASYLUM SEEKERS AND INDEPENDENT REFUGEES IN INDONESIA - Raihan Pratama; Surya Pranata (Polteknik Imigrasi, 2022)
ABSTRACT This research is motivated by the main problem in asylum seekers and refugees in Indonesia, namely the distribution of asylum seekers and independent refugees who are not recorded by the Directorate General of Immigration so that many of their existence and activities are not monitored. This study aims to explore the efforts that have been made by the Directorate General of Immigration in optimizing cooperation with IOM and UNHCR in handling asylum seekers and independent refugees in Indonesia and to establish an ideal form of cooperation between the Directorate General of Immigration with IOM and UNHCR in optimizing the handling of asylum seekers. and independent refugees in Indonesia. This research method uses Normative-Empirical which is essentially a combination of normative legal approaches with the addition of empirical elements. The normative-empirical legal research category used is Live Case Study. State Sovereignty Theory and International Cooperation Theory are used in this study. The results of this study found the problems faced by the Directorate General of Immigration both from the UNHCR, IOM, and internal DITJENIM itself in handling asylum seekers and independent refugees in Indonesia and forming an ideal cooperation agreement because previously there had never been between the Directorate General of Immigration with IOM and UNHCR in optimizing the handling of asylum seekers and independent refugees in Indonesia. Keywords: Cooperation, Handling, Independent Refugee ABSTRAK Penelitian ini dilatarbelakangi oleh permasalahan utama dalam pencari suaka dan pengungsi di Indonesia yaitu persebaran pencari suaka dan pengungsi mandiri yang tidak terdata oleh Direktorat Jenderal Imigrasi sehingga banyak dari keberadaan serta kegiatan mereka yang tidak terawasi. Penelitian ini bertujuan untuk mendalami upaya yang telah dilakukan oleh Direktorat Jenderal Imigrasi dalam mengoptimalkan kerja sama dengan IOM dan UNHCR dalam penanganan pencari suaka dan pengungsi mandiri di Indonesia dan membentuk bentuk kerja sama yang ideal antara Direktorat Jenderal Imigrasi dengan IOM dan UNHCR dalam optimalisasi penanganan pencari suaka dan pengungsi mandiri di Indonesia. Metode penelitian ini menggunakan Normatif-Empiris yang pada hakikatnya penggabungan antara pendekatan hukum normatif dengan adanya penambahan unsur-unsur empiris, kategori penelitian hukum Normatif-empiris yang digunakan ini adalah Live Case Study. Teori Kedaulatan Negara dan Teori Kerja Sama Internasional digunakan dalam penelitian ini. Hasil dari peneltian ini menemukan permasalahan-permasalahan yang dihadapi oleh Direktorat Jenderal Imigrasi baik dari sisi UNHCR, IOM, dan internal DITJENIM itu sendiri dalam melakukan penanganan pencari suaka dan pengungsi mandiri di Indonesia serta membentuk perjanjian kerja sama yang ideal dikarenakan sebelumnya belum pernah ada antara Direktorat Jenderal Imigrasi dengan IOM dan UNHCR dalam optimalisasi penanganan pencari suaka dan pengungsi mandiri di Indonesia. Kata Kunci: Kerja Sama, Penanganan, Pengungsi Mandiri